The physico-chemical and antimicrobial properties of nano ZnO functionalised tannic acid - Nurul Akmal, Che Lah; Aqilah, Kamaruzaman (Nature Research, 2024)
Tannic acid (TA) has been reported as an efficient plant-based compound with inhibitory activity against viruses and bacteria. The combination of TA with Zinc Oxide (ZnO) nanostructures with ZnO is one of the most widely used nanoparticles for antimicrobial properties, have not yet fully elucidate especially their mechanisms of overall physicochemical and antimicrobial actions. Hence, to observe the influence of TA adsorption on ZnO, the investigations on the TA concentration and the effect of pH towards the physicochemical, optical and antimicrobial properties are demonstrated. The pure ZnO are synthesised via the chemical reduction method and the ZnO-TA nanostructures are further prepared using the dropwise methods to form variations of pH samples, which causes the formation of different mean particle size distribution, dm. The findings reveal that the performance of physicochemical and optical properties of pure ZnO and ZnO-TA are different due to the wrapped layers of TA which change the charged surface of all the particles. The protonation reactions yield strong pH dependence (pH 3 and 5), with uptake performance becoming more dominant at higher TA concentration loading (pH 3). The detailed optical energy bandgap and Urbach energy that concluded the nanoparticle growth and disorder condition of produced particles are presented. For antimicrobial efficiency, ZnO-TA shows improved effectiveness in growth inhibitions of S. aureus 99.69% compared to pure ZnO nanostructure (99.39%). This work reveals that the TA concentration increases the overall performance, and the discussion gives added support to their potential performance related to the field of ZnO compound.